Nexus between Non-Performance Loans and Financial Performance of Commercial Banks Listed at Dse, Tanzania: Ardl Approach - James Daniel Chindengwike (HM Journals, 2022)
Management of credit risk is serious to the financial viability of commercial banks in both developing and developed countries. Non-performing loans (NPLS) are proxies for credit risk. The study investigated the association between NPLs and the financial performance of Tanzanian commercial banks. The study used a causal research design, with study participants NMB, CRDB MKOMBOZI, MAENDELEO, and DCB recruited by a purposeful selection approach. The research was based on secondary data received from the DSE between 2013 and 2020. Making use of a template collection. Descriptive statistics, a correlation matrix for a link, bound cointegration for a long-run relationship, the granger causal test for a causal association, and an error correction model were employed in the study. According to the study's findings, there is a significant negative relationship between financial performance and NPLs. It. The investigation found that there is a long-run relationship between the factors under consideration and financial performance. Furthermore, a one-way association was established between NPLs and the financial performance of CRDB NMB, MAENDELEO, DCB and MKOMBOZI, the survey found that commercial banks listed on the DSE had a low rate of NPLs. While the issue was interesting, close is an essential to do a complete examination of all Tanzanian banks.